(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Background: There has been a growing interest in childhood neuromuscular diseases due to the advancement of neurophysiological tests in Bangladesh recently. This diagnostic tool is very useful in identifying various neuromuscular disorders. This study aims to observe the electro-clinical profile of patients with suspected neuromuscular diseases referred to a neurophysiology laboratory. Methodology: This cross-sectional study was conducted in the Neurophysiology Laboratory of the Paediatric Neuroscience Department at Bangladesh Shishu Hospital and Institute from May 1st, 2024, to April 30th, 2025. During this period, children with suspected neuromuscular disease underwent nerve conduction studies and, when appropriate, needle electromyography (EMG). Demographic and clinical data were collected from the referral notes and from the parents. Results: Among 115 children with suspected neuromuscular disease, the most common presenting complaints were acute flaccid paralysis (40%), progressive limb weakness (28.7%), and traumatic injury (13%). Other symptoms included limb pain (10.4%), generalized floppiness (5.2%), periodic paralysis (1.7%), and isolated facial nerve palsy (0.9%). Nerve conduction studies (NCS) showed abnormalities in 67.8% in cases. EMG was performed in 26(22.6%). 15.65% participants showed abnormal EMG findings. Guillain-Barré Syndrome was the most common electro diagnosis (40%), followed by traumatic neuropathy (7%), non-inflammatory myopathy (6%), spinal muscular atrophy (5.2%), polyneuropathy (3.5%), inflammatory myopathy (2.6%), motor neuron disease (1.7%), plexopathy (1.7%), and facial nerve palsy (0.9%). Abnormal electrodiagnostic findings were significantly associated with suspected GBS, progressive disease course, and non-specific/symptom-based referral diagnosis, while age and sex showed no significant association. Conclusion: This study highlights the high diagnostic yield of electrodiagnostic testing in children with suspected neuromuscular disorders, with nearly two-thirds demonstrating abnormal NCS findings. Abnormal electrodiagnostic findings were significantly associated with suspected GBS, progressive disease course, and non-specific/symptom-based diagnosis, emphasizing the importance of appropriate clinical diagnosis. J Bangladesh Coll Phys Surg 2026; 44: 103-110